2018
DOI: 10.1007/s40430-017-0943-1
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of functionally graded graphene-reinforced nanocomposite beams with temperature-dependent properties

Abstract: A temperature-dependent vibration analysis is conducted for the functionally graded nanocomposite beams which are reinforced by graphene. Material properties are assumed to change along the beams in five different types based upon the graphene distribution with a specific function. The differential equations of motion are extracted and solved using the spectral numerical method for the beams under various boundary conditions. The effect of distribution of functionally graded nanocomposite in the thickness dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Researches proved that subjoining even a very meager amount of graphene into primary polymer matrix can desperately improve its mechanical, thermal and electrical properties [5][6][7][8][9]. It is worse to mention that nanostructures reinforced with GNP are more applicable in engineering design, so focus on dynamic modeling of the nanostructure with GNP reinforcement is useful and important.…”
Section: Introductionmentioning
confidence: 99%
“…Researches proved that subjoining even a very meager amount of graphene into primary polymer matrix can desperately improve its mechanical, thermal and electrical properties [5][6][7][8][9]. It is worse to mention that nanostructures reinforced with GNP are more applicable in engineering design, so focus on dynamic modeling of the nanostructure with GNP reinforcement is useful and important.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that GPLs with a bigger surface area and comprising fewer single-GPL laminates may provide better reinforcing influence; however, for GPL aspect ratios and widthto-thickness ratios more than 4 and 1000, critical buckling force and post-buckling path will be almost identical. Furthermore, many studies have been implemented to show that functionally graded nanofiller distribution patterns also play a key role in the structural response of composite structures (Pradhan and Phadikar, 2010;Lei et al, 2015;Zhang et al, 2015;Bui et al, 2016;Lin et al, 2017;Ansari et al, 2018;García-Macías et al, 2018;Lin et al, 2018;Muni Rami Reddy et al, 2018;Shahrjerdi and Yavari, 2018;Yang et al, 2018;Nguyen et al, 2019;Thai et al, 2019;Hung et al, 2021;Saiah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A functionally graded material (FGM) is a novel type of composite in which the mechanical properties vary smoothly and continuously in a preferred direction [2][3][4][5]. For better utilization of the superior mechanical properties of carbon nanofillers and inspired from the concept of FGMs, functionally graded carbon nanotube-reinforced composites (FG-CNTRCs) [6][7][8] and functionally graded graphene nanoplatelet-reinforced composites (FG-GPLRCs) [9][10][11] have been introduced, in which the weight fractions of CNTs and GPLs vary in the thickness direction.…”
Section: Introductionmentioning
confidence: 99%